If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 7 = 3(x + 4) Reorder the terms: 7 + 5x = 3(x + 4) Reorder the terms: 7 + 5x = 3(4 + x) 7 + 5x = (4 * 3 + x * 3) 7 + 5x = (12 + 3x) Solving 7 + 5x = 12 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 7 + 5x + -3x = 12 + 3x + -3x Combine like terms: 5x + -3x = 2x 7 + 2x = 12 + 3x + -3x Combine like terms: 3x + -3x = 0 7 + 2x = 12 + 0 7 + 2x = 12 Add '-7' to each side of the equation. 7 + -7 + 2x = 12 + -7 Combine like terms: 7 + -7 = 0 0 + 2x = 12 + -7 2x = 12 + -7 Combine like terms: 12 + -7 = 5 2x = 5 Divide each side by '2'. x = 2.5 Simplifying x = 2.5
| .74=11612000-x/5246000 | | 1+192837465x-d=231111111116666666 | | 4/b-7/d= | | 55x-9+g=100007 | | 4/(x-6)=5 | | 55x-9+g= | | 3t+19-5t=91 | | z^2(4z^3-10)=0 | | u/4=0 | | 5p^2+30x=0 | | 4x-1=2(x-5) | | 5c+17-8c=156 | | 2=p/6 | | 5/60=w/10 | | 4x-1=2(x-3) | | 345=874-x/874 | | 9r+9= | | 2x-1/4x=(-28) | | 3/4d=18 | | 7(x+8)+4=-9(x-9)-1 | | 2s+a=447 | | 3/8d=6 | | X+11x+2=0 | | 3(4x+1)=9(3x-5) | | 6x-4=5(x+3)+7 | | 3x^2-18x=48 | | 81x^3+324x^2-x-4=0 | | 7x-8-4x=25 | | y=-3/5x-4/5 | | (3+x)3=9 | | 2x-13=7*12 | | -5-(15y-1)=2(7y-6)+y |